Retail payment innovations and cash usage: Accounting for attrition using refreshment samples - Heng Chen; Marie-Hélène Felt; Kim P. Huynh (Bank of Canada, 2014)
We exploit the panel dimension of the Canadian Financial Monitor (CFM) data to estimate the impact of retail payment innovations on cash usage. We estimate a semiparametric panel data model that accounts for unobserved heterogeneity and allows for general forms of non-random attrition. We use annual data from the CFM on the methods of payment and cash usage for the period 2010 - 12. Estimates based on crosssectional methods find a large impact of retail payment on cash usage (around 10 percent). However, after correcting for attrition, we find that contactless credit cards and multiple stored-value cards (reloadable) have no significant impact on cash usage, while single-purpose stored-value cards reduce the usage of cash by 2 percent in terms of volume. These results point to the uneven pace of the diffusion of payment innovations, especially contactless credit. – – Les auteurs mettent à profit la dimension panel des données provenant de l'enquête Canadian Financial Monitor (CFM) pour évaluer l'impact de certains nouveaux instruments de paiement au détail sur le règlement en espèces des transactions. Ils estiment un modèle de données de panel semi-paramétrique qui tient compte de l'hétérogénéité non observée et de l'attrition non aléatoire. Ils utilisent des données annuelles tirées des enquêtes CFM sur les méthodes de paiement et le recours au comptant pour la période 2010-2012. Selon des estimations fondées sur une analyse transversale, les instruments de paiement au détail ont une grande incidence (évaluée à environ 10 %) sur l'utilisation de l'argent comptant. Toutefois, une fois l'attrition prise en compte, il ressort que les cartes de crédit sans contact et les cartes prépayées multiusages rechargeables n'ont pas un effet significatif sur l'utilisation du numéraire, tandis que les cartes prépayées à usage spécifique réduisent le recours au comptant d'environ 2 % en volume. Ces résultats mettent en évidence le rythme inégal de diffusion des innovations, en particulier les cartes de crédit sans contact.
Keywords: E41; C35; 330; E-money; Bank notes; Econometric and statistical methods; Financial services